Association Between Single Nucleotide Polymorphisms in CDKAL1 and HHEX and Type 2 Diabetes in Chinese Population - Li C (Dove Medical Press, 2021)
Chuanyin Li,1,* Keyu Shen,2,* Man Yang,3 Ying Yang,3 Wenyu Tao,3 Siqi He,4 Li Shi,1 Yufeng Yao,1 Yiping Li3 1Institute of Medical Biology, Chinese Academy of Medical Sciences & Peking Union Medical College, Kunming, Yunnan 650118, People’s Republic of China; 2Department of Medicine, Dentistry and Healthy Science, The University of Melbourne, Melbourne, VIC 3010, Australia; 3Department of Endocrinology and Metabolism, The Second People’s Hospital of Yunnan Province, & the Affiliated Hospital of Yunnan University, Kunming, Yunnan 650021, People’s Republic of China; 4School of Clinical Medicine, Dali University, Dali, Yunnan 671000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yufeng YaoInstitute of Medical Biology, Chinese Academy of Medical Sciences & Peking Union Medical College, Kunming, 650118 Yunnan, People’s Republic of ChinaEmail yufeng_yao@imbcams.com.cnYiping LiDepartment of Endocrinology and Metabolism, The Second People’s Hospital of Yunnan Province & the Affiliated Hospital of Yunnan University, Kunming, 650021 Yunnan, People’s Republic of ChinaEmail yyflyp@aliyun.comPurpose: Type 2 diabetes mellitus (T2DM) has a high global prevalence, and the interaction of environmental factors and genetic factors may contribute to the risk of T2DM. We aimed to investigate the association between T2DM and the single nucleotide polymorphisms (SNPs) in genes (CDKAL1 and HHEX) associated with insulin secretion.Subjects and Methods: T2DM (n=1,169) and nondiabetic (NDM) (n=1,277) subjects were enrolled and the eight SNPs in CDKAL1 and HHEX genes associated with insulin secretion were genotyped in a Chinese population using MassARRAY. Then, the association of these SNPs with T2DM was analyzed.Results: Our results revealed that four SNPs (rs4712524, rs10946398, rs7754840 in CDKAL1, and rs5015480 in HHEX) showed significantly different distributions between the T2DM and NDM groups (P< 0.00625). The G allele of rs4712524 (P=0.004, OR=1.184; 95% CI=1.057– 1.327), C allele of rs10946398 (P< 0.001, OR=1.247; 95% CI=1.112– 1.398), and C allele of rs775480 in CDKAL1 (P< 0.001, OR=1.229; 95% CI=1.096– 1.387) functioned as risk alleles of T2DM. The C allele of rs5015480 in HHEX (P< 0.001, OR=1.295; 95% CI=1.124– 1.493) was also the risk factor for T2DM. The haplotype analysis revealed that CDKAL1 haplotype rs4712524G-rs10946398C-rs7754840C-rs9460546G (P=0.001, OR=1.210; 95% CI=1.076– 1.360) and HHEX haplotype rs1111875C-rs5015480C (P< 0.001, OR=1.364; 95% CI=1.180– 1.576) were the risk factors of T2DM.Conclusion: Our results revealed that genetic variations in CDKAL1 and HHEX were associated with T2DM susceptibility in Chinese population.Keywords: association study, single nucleotide polymorphisms, CDKAL1, HHEX, type 2 diabetes, Chinese population